2003
DOI: 10.1016/j.jasms.2003.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Direct dynamics study ofN-protonated diglycine surface-induced dissociation. Influence of collision energy

Abstract: A quantum mechanical and molecular mechanical (QM + MM) direct dynamics classical trajectory simulation is used to study energy transfer and fragmentation in the surface-induced dissociation (SID) of N-protonated diglycine, (gly)2H+. The peptide ion collides with the hydrogenated diamond [111] surface. The Austin Model 1 (AM1) semiempirical electronic structure theory is used for the (gly)2H+ intramolecular potential and molecular mechanical functions are used for the diamond surface potential and peptide/surf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
79
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(87 citation statements)
references
References 43 publications
7
79
1
Order By: Relevance
“…The distributions of energy-transfer to ⌬E int , ⌬E surf , and E f , for the i ϭ 0°collisions, are shown in Figure 2. Their forms are similar to those found previously [6,9,10,14,17,18] for simulations of the smaller gly n -H ϩ peptide ions and for the current study with i ϭ 45°.…”
Section: Energy Transfer Efficienciessupporting
confidence: 90%
See 2 more Smart Citations
“…The distributions of energy-transfer to ⌬E int , ⌬E surf , and E f , for the i ϭ 0°collisions, are shown in Figure 2. Their forms are similar to those found previously [6,9,10,14,17,18] for simulations of the smaller gly n -H ϩ peptide ions and for the current study with i ϭ 45°.…”
Section: Energy Transfer Efficienciessupporting
confidence: 90%
“…For the work presented here, the much less expensive QM method AM1 was used. Previous work has shown that nearly the same energy-transfer efficiencies are obtained when either AMBER, AM1, or MP2/ 6-31G* are used to represent the peptide ion's intramolecular potential V ion [6,9,10,14]. In chemical dynamics simulations of gly-H ϩ SID, the same shattering probabilities are obtained when using either AM1 or MP2/6-316* for V ion [10,14].…”
Section: Potential Energy Functionmentioning
confidence: 67%
See 1 more Smart Citation
“…Hase and colleagues have shown that several factors affect kinetic to internal energy conversion in the SID process, including collision energy, peptide size and conformation, incident collision angle, and surface target. Classical trajectory simulations of protonated diglycine and dialanine demonstrated that internal energy transfer in normal-incidence SID (collision perpendicular to the surface) decreases slightly with increasing collision energy [101,102]. The influence of peptide size has been explored by examining collisions of polyglycine (gly n -H ϩ , n ϭ 1-5) with a diamond surface.…”
Section: Characterization Of Energy Deposition In Peptide Ion-surfacementioning
confidence: 99%
“…Simulations of glycine colliding with a diamond surface revealed that as much as 55% of the total fragmentation observed could be attributed to shattering at the surface [99]. For simulations on diglycine, the shattering mechanism resulted in an increase in the number of fragmentation channels available from 6 at 30 eV to 59 at 100 eV and was strongly influenced by the orientation of the diglycine molecule as it collided with the surface [101].…”
Section: Kinetics Of Peptide Fragmentationmentioning
confidence: 99%